2019
DOI: 10.1097/bpb.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells as adjuvant therapy for limb lengthening in achondroplasia

Abstract: Staged leg lengthening allows achondroplastic dwarfs to reach nearly normal height, but it takes long periods of external fixation and it can be burdened by delayed unions. Between 2009 and 2013, eight achondroplastic dwarfs showed delayed unions in the callus formation during femoral lengthening stages in our institute. We performed in-situ injections of bone marrow-derived stem cell concentrates. Patients underwent monthly clinical and radiographic assessment for determination of the healing rate. All eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Bone marrow aspirate used in the treatment of osteonecrosis during the minimally invasive decompression of the femoral head halted the progression of the disease and resulted in pain relief [165]. Analogically, delayed unions existing after femoral lengthening surgeries in achondroplastic dwarfs were improved by adjuvant in-situ therapy performed using injections of bone marrow concentrate, with complete recovery taking 2-10 months in all patients [166]. Nonetheless, a study aiming to enhance the biomechanical properties of distraction osteogenesis (DO) by supplementation of distracted bone with bone marrow aspirate concentrate (BMAC) delivered non-significant results and failed to improve bone strength [167].…”
Section: Bone Marrow Mononuclear Cells and Bone Marrow Concentratementioning
confidence: 99%
“…Bone marrow aspirate used in the treatment of osteonecrosis during the minimally invasive decompression of the femoral head halted the progression of the disease and resulted in pain relief [165]. Analogically, delayed unions existing after femoral lengthening surgeries in achondroplastic dwarfs were improved by adjuvant in-situ therapy performed using injections of bone marrow concentrate, with complete recovery taking 2-10 months in all patients [166]. Nonetheless, a study aiming to enhance the biomechanical properties of distraction osteogenesis (DO) by supplementation of distracted bone with bone marrow aspirate concentrate (BMAC) delivered non-significant results and failed to improve bone strength [167].…”
Section: Bone Marrow Mononuclear Cells and Bone Marrow Concentratementioning
confidence: 99%
“…The association of EF with an internal fixation system (elastic stable intramedullary nails, rigid intramedullary nails, and MIPO plates) has been widely reported, with a significant reduction in the EF bearing time in all cohorts. Other authors demonstrated that physical and/or biological bone stimulations with low-intensity pulsed ultrasounds (LIPUSs), pulsed electromagnetic fields (PEMFs), bone marrow concentrate (BMC), or platelet-rich plasma (PRP) injections in the regenerate area after distraction osteogenesis may all significantly decrease the time spent in EFs [27,28]. All these strategies can be truly effective; however, the potentially increased risks of additional surgical procedures and the extra costs must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Current research in limb lengthening has been based on the experiments which are aimed at distraction osteogenesis acceleration and faster regenerate maturation that take many months to complete efficient bone formation. The protocol of injecting bone marrow aspirate concentrate in multiple areas of poor regenerate was used to correct delayed union in achondroplasia during distraction osteogenesis, but the study evokes concerns of bias in confirming its role for faster healing[ 75 ]. Several studies used pharmacological agents to improve regenerate formation.…”
Section: Current Clinical Practice and Research In The Ilizarov Techniques Of Bone Reconstructionmentioning
confidence: 99%